Estudo prospectivo de fatores de risco para doenças cardiovasculares em sobreviventes ao câncer de mama em uso de inibidores de aromatase - Mazzutti, Fernanda Silva (2020)
Background: The increased risk for the occurrence of cardiovascular diseases in breast cancer (BC) survivors has been widely discussed in the literature and occurs due to the cardiotoxicity of antineoplastic treatments and also to the common risk factors between these diseases. Objectives: To evaluate the risk factors for cardiovascular diseases (anthracycline chemotherapy, radiotherapy, diabetes mellitus, hypertension, inadequate diet, excess body weight, abdominal adiposity, alcoholism, smoking, physical inactivity and altered lipid profile) in BC women surviving in use of endocrine therapy with Aromatase Inhibitors (AI). Material and methods: A prospective study was conducted with a follow-up time of 24 months and evaluations in three stages, called T0, the initial follow-up period; T1, intermediate period, corresponding to 12 months after T0; and T2, the final follow-up period, corresponding to 24 months after T0. Treatments and BC clinical data were obtained through the analysis of medical records. Questionnaires containing information on sociodemographic data, comorbidities, smoking, alcoholism, physical inactivity, food consumption and anthropometric variables were collected in the three periods. Food consumption was assessed using three 24-hour food records at each time, and its qualitative analysis was performed by calculating the Revised Diet Quality Index (IQDR). For the evaluation of biomarkers related to cardiovascular risk (total cholesterol, low-density lipoprotein (LDL), high-density lipoprotein (HDL), non-HDL cholesterol and triglycerides), samples of venous blood were collected. Results: Most women underwent cardiotoxic treatments such as anthracycline chemotherapy (60.9%) and radiotherapy (84.3%). We verify a predominance of inadequacy of the IQD-R food groups, except for oils, in addition to inadequate consumption of total, saturated, monounsaturated fats and fibers in the three periods. We found that the Body Mass Index did not change over the three times, but there was a predominance of inadequacy (T0 = 60.7%; T1 = 64.6%; T2 = 65.8%). There was an increase in waist circumference and waist-height ratio (p = 0.027 and p = 0.029) between T0 and T1, with inadequacy at all times. As for biochemical data, there was a reduction in total cholesterol (p = 0.013), LDL (p = 0.010) and non-HDL cholesterol (p = 0.004) from T1 to T2. There was a high percentage of systemic arterial hypertension (T0 = 56.2%; T1 = 58.5%; T2 = 55.3%) and physical inactivity (T0 = 59.6; T1 = 47.7%; T2 = 57.9%) throughout the study. There were no alcoholic women in the three periods of the study. As for the number of risk factors, most women had between 6 and 10 risk factors for CVDs. Conclusion: Despite showing improvement in the lipid profile and not being alcoholics, most BC survivors using AI had a worrying amount of CVD risk factors at all times in the study. Thus, we suggest the necessity to carry out interventions in this population aiming at food reeducation and encouraging regular physical activity.